Assessment of genotoxicity of pyrethrin in cultured human lymphocytes. (3rd July 2017) - Azab, Mohammad; Khabour, Omar F.; Alzoubi, Karem H.; Hawamdeh, Hasan; Quttina, Maram; Nassar, Liliana
Abstract: Pyrethrin is an insecticide that is obtained from the Chrysanthemum flower (Pyrethrum). In this study, we examined the genotoxic effects of pyrethrin on cultured human lymphocytes using sister chromatid exchanges (SCEs) and 8-hydroxy deoxyguanosine (8-OHdG) assays. Cultures were treated with different concentrations of pyrethrin (25, 50, and 100 μg/mL), which was dissolved in in dimethyl sulfoxide (DMSO). The results showed that treatment of cultured lymphocytes with pyrethrin at 50 μg/mL and 100 μg/mL induced significant elevation in SCEs ( p  < 0.05). In addition, the 100 μg/mL concentration significantly affected both mitotic and proliferative indices ( p  < 0.05). Finally, pyrethrin induced significant elevation in the oxidative stress marker 8-OHdG in a dose-dependent manner ( p  < 0.001). In conclusion, the results suggest that pyrethrin is genotoxic as measured by two independent assays on genetic toxicity.